2020
DOI: 10.3390/ani10040623
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Aggressions between Crested Porcupines and Roe Deer

Abstract: Despite being common amongst carnivore mammals, behavioral interference between wild herbivore species is poorly documented. Particularly, in temperate areas, where the ungulate guild is composed of a few species, and large-sized rodents are scarce, most cases of interspecific interactions involve at least one alien species. In this work, we report the first data on behavioral interactions between roe deer, Capreolus capreolus, and crested porcupine, Hystrix cristata. Aggressions by crested porcupines toward r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Taxa with spines (or foam-cored quills) include echidnas (Tachyglossidae), tenrecs (Tenrecinae), hedgehogs (Erinaceinae), Afro-Eurasian porcupines (Hystricidae), and American porcupines (Erethizontidae), with spines evolving independently in each lineage. The extremely long quills of Afro-Eurasian porcupines (Figure 1F) and the barbed quills of American porcupines can seriously injure and even kill attacking predators (Afro-Eurasian: Mori et al, 2014;Kerbis Peterhans et al, 2019;Lazzeri et al, 2020;American: Katzner et al, 2015;Elbroch et al, 2016;Forti et al, 2018). These structures will therefore deter predators for risk of physical harm and incapacitation.…”
Section: Mammalsmentioning
confidence: 99%
“…Taxa with spines (or foam-cored quills) include echidnas (Tachyglossidae), tenrecs (Tenrecinae), hedgehogs (Erinaceinae), Afro-Eurasian porcupines (Hystricidae), and American porcupines (Erethizontidae), with spines evolving independently in each lineage. The extremely long quills of Afro-Eurasian porcupines (Figure 1F) and the barbed quills of American porcupines can seriously injure and even kill attacking predators (Afro-Eurasian: Mori et al, 2014;Kerbis Peterhans et al, 2019;Lazzeri et al, 2020;American: Katzner et al, 2015;Elbroch et al, 2016;Forti et al, 2018). These structures will therefore deter predators for risk of physical harm and incapacitation.…”
Section: Mammalsmentioning
confidence: 99%
“…In central and southern Tanzania, the range of H. cristata partly overlaps with that of the closely related H. africaeaustralis Peters, 1852 (Trucchi and Sbordoni 2009). The ecology of this species, i.e., orientation (Massolo et al 2009), use of den setts (Pigozzi 1986;Monetti et al 2005), habitat use/selection (Pigozzi and Patterson 1991;Mori et al 2014a;Mori 2017), patterns of activity rhythms (Mori et al 2014c;Lovari et al 2017), diet (Bruno and Riccardi 1995), reproductive behaviour (Mori et al 2016) and interspecific interactions (Mori et al 2014b;Lazzeri et al 2020) have been studied mostly in the introduced range, i.e., in Italy. Ecology and behavioural biology of the crested porcupine in its native range are mostly unknown, a part from a study on its diet in Tunisia (Ettiss et al 2020), which reported that this rodent is mostly a consumer of grasses and cultivated species.…”
Section: Introductionmentioning
confidence: 99%